An Analysis Of Students’ Equivalence In Translating English Idiom In Narrative Text Into Bahasa Indonesia - ELSA ANDIKA FEBRIANI (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2023)
The aim of this research was to investigate and learn how the students to equating translation English idiom in narrative text into Bahasa Indonesia at the fourth semester of English department Bhinneka PGRI Univercity of the 2021/2022 Academic Year. A qualitative descriptive approach in this research. A qualitative descriptive approach was used to measure students' abilities in a thorough analysis to determine students' abilities in translating idioms in narrative text using test documentation with 11 research students in one class. The instrument used in the data collection was a interview and documentation test. The first step is to find out students' perceptions in translating English idioms into Indonesian. and test documentation is used to measure students' ability in working on idiom narrative text translation problems. The data were analyzed using statistical and shown in table of frequency.This finding shows that students of narrative text can be one of the alternative media for students in learning to translate idioms using good translation equivalence.